(untitled) (Comprehensive Journal of Science, 2025)
The excessive discharge of toxic metals into water bodies, a consequence of increased production, has become a major environmental problem due to the inefficiency of technologies used to treat industrial wastewater. These metals accumulate at high toxic levels, causing serious effects on aquatic organisms without any apparent trace. They can cause poisoning or toxic effects even at low concentrations. These toxic heavy metals include cadmium, manganese, copper, lead, nickel, cobalt, and chromium. They are highly toxic once ingested, affecting humans and animals directly, and indirectly through the food chain. This paper investigates the feasibility of using low-biomass waste to adsorb lead Pb (II) ions of a specific concentration from aqueous solutions, and the effect of the initial concentration on adsorption efficiency on the surface of flake eggshells.